Cuantificación de antocianinas totales y capacidad antioxidante del fruto de Sambucus peruviana (sauco) - Cuba Gomero, Anthony Lenin (2019)
The objective of this research was to determine the total anthocyanin content and antioxidant capacity of the Sambucus peruviana "sauco" fruit from the town of San José de Porcón, district of Quiruvilca, province of Santiago de Chuco, La Libertad region, method: The plant species was collected, selected in its fresh, mature, heavy state and identified in the Herbarium Truxillense of the National University of Trujillo, to be processed, total anthocyanins were quantified by the differential pH method and the antioxidant capacity was evaluated by means of the DPPH method (2,2 diphenyl-1-picrylhydrazyl). Results; The total anthocyanin concentration of 7.094 ± 0.07 mg expressed in cyanidin-3-o-glucoside / 100 g fresh sample and the antioxidant capacity of 31.3736 ± 0.07 mg expressed ascorbic acid / 100 g fresh sample was determined